Effect of arbuscular mycorrhizal fungi on the responses of Ageratina adenophora to Aphis gossypii herbivory - Du, Ewei; Chen, Yaping; Li, Yahong; Zhang, Fengjuan; Sun, Zhongxiang; Hao, Ruoshi; Gui, Furong (Frontiers in Plant Science, 2022)
The invasive weed Ageratina adenophora can form a positive symbiotic relationship with native arbuscular mycorrhizal fungi (AMF) to promote its invasion ability. However, the function of AMF during the feeding of Aphis gossypii in A. adenophora was poorly understand. This study aimed to investigate the effects of two dominant AMF (Claroideoglomus etunicatum and Septoglomus constrictum) on A. adenophora in response to the feeding of the generalist herbivore A. gossypii. The results showed that A. gossypii infestation could significantly reduce the biomass, nutrient and proline contents of A. adenophora, and increase the antioxidant enzyme activities, defense hormone and secondary metabolite contents of the weed. Compared with the A. gossypii infested A. adenophora, inoculation C. etunicatum and S. constrictum could significantly promote the growth ability and enhanced the resistance of A. adenophora to A. gossypii infestation, and the aboveground biomass of A. adenophora increased by 317.21% and 114.73%, the root biomass increased by 347.33% and 120.58%, the polyphenol oxidase activity heightened by 57.85% and 12.62%, the jasmonic acid content raised by 13.49% and 4.92%, the flavonoid content increased by 27.29% and 11.92%, respectively. The survival rate of A. gossypii and density of nymphs were significantly inhibited by AMF inoculation, and the effect of C. etunicatum was significantly greater than that of S. constrictum. This study provides clarified evidence that AMF in the rhizosphere of A. adenophora are effective in the development of tolerance and chemical defense under the feeding pressure of insect herbivory, and offer references for the management of the A. adenophora from the perspective of soil microorganisms.